Repercussões de Brecht, o pós-dramático e as novas tecnologias em Máquina de Pinball. - Gil de Medeiros Esper (2009)
This paper alms to investigate the repercussion of epic-dialectical theater, mainly in the matter of distance effect achieved through irony, allied to issues raised by the post-dramatic theater. To know: the performatic, the new technologies and the new ways of spectacular reception in a specific work, which is the play Máquina de Pinball (Pinball Machine), presented at 2008 in Belo Horizonte, Brazil.